Answer:
Below, depends if 27 is term number 1 or term number 0. Answered for both cases.
Step-by-step explanation:
The most common sequences are arithmetic and geometric, so lets check those first.
Arithmetic first since its the easiest.
to go from 27 to 21 we subtract 6, if we subtract 6 from 21 again we get to 15, which is what we need, so it is indeed arithmetic.
Explicit formula is basically of the form of y=mx+b with an arithmetic sequence. the m is the common difference and b is the first term minus the common difference. so lets fill those in. y = -6x + 33
Then it usually has n as the x and y f(n) so we'll just put those in
f(n) = -6n + 33
This si as long as the first term is labeled as term number 1 and not term number 0. if you have 27 as term 0 instead just make 33 back to 27, so f(n) = -6n + 27
Let me know if this doesn't make sense.
Answer:
The answer you're looking for is
-5r (3r^2) = -45
Step-by-step explanation:
Answer:
Ok, we have a system of equations:
6*x + 3*y = 6*x*y
2*x + 4*y = 5*x*y
First, we want to isolate one of the variables,
As we have almost the same expression (x*y) in the right side of both equations, we can see the quotient between the two equations:
(6*x + 3*y)/(2*x + 4*y) = 6/5
now we isolate one off the variables:
6*x + 3*y = (6/5)*(2*x + 4*y) = (12/5)*x + (24/5)*y
x*(6 - 12/5) = y*(24/5 - 3)
x = y*(24/5 - 3)/(6 - 12/5) = 0.5*y
Now we can replace it in the first equation:
6*x + 3*y = 6*x*y
6*(0.5*y) + 3*y = 6*(0.5*y)*y
3*y + 3*y = 3*y^2
3*y^2 - 6*y = 0
Now we can find the solutions of that quadratic equation as:
So we have two solutions
y = 0
y = 2.
Suppose that we select the solution y = 0
Then, using one of the equations we can find the value of x:
2*x + 4*0 = 5*x*0
2*x = 0
x = 0
(0, 0) is a solution
if we select the other solution, y = 2.
2*x + 4*2 = 5*x*2
2*x + 8 = 10*x
8 = (10 - 2)*x = 8x
x = 1.
(1, 2) is other solution
angle 1 = 180-110 = 70 degrees (linnear pair)
angle 2= 180-115 = 65 degrees (linnear pair)
angle 3 = angle 2 = 65 degrees (corresponding angles)
angle 4= 180 - angle 3 = 180-65 = 115 degrees (linnear pair)
(your teacher might not like this, depends on the cituation, but use 180 degrees in triangle to get 7)
angle 7 = 180 -angle1 -angle 2= 180-70-65= 45 degrees
angle 6 = angle 7 = 45 degrees ( vertical angles)
angle 8= 180- angle 7= 180-45 = 135 ( linnear pair)
angle 9 =angle 6 = 45 degrees (corresponding angles)
angle 5=angle 9=45 degrees (vertical angles)
0.8 is greater because it is a positive number..